Relationship of Knowledge, Attitudes and Behavior of Parents About Stimulation with Two - Tetti Seriati Situmorang; Juliani; Ernamari; Ira Agustina (Science Midwifery, 2022)
The age of a baby of two years is the golden phase of a child's growth where the brain's capacity is maximally developed. This phase is an essential period in the process of developing children's skills and intelligence which will have a major influence on life as adults. Parents have a responsibility as the main caregivers of children from an early age. This study aims to see the relationship between knowledge, attitudes and behavior of parents about stimulation with the development of a two-year-old baby at the Batahan Health Center. The research design was analytic observational with cross sectional. The population in this study were mothers who had babies aged 21-24 months in June 2022 in the working area of ​​the Batahan Health Center, Mandailing Natal district. The number of samples as many as 61 people obtained using simple random sampling technique, data analysis using Chi-square test. The results obtained on the knowledge variable p-value 0.574> 0.05, the attitude variable p-value 0.727> 0.05 means that there is no relationship between knowledge and parental attitudes about stimulation of toddlers with 2-year-old toddler development, and the behavior variable p-value 0.000 <0.05 means that there is a relationship between parental behavior regarding toddler stimulation and the development of a 2-year-old toddler. The conclusion of this study is that there is no relationship between knowledge and attitudes of parents about toddler stimulation with 2-year-old child development and there is a relationship between parental behavior regarding